If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + 16 = 2r + 1 Reorder the terms: 16 + r = 2r + 1 Reorder the terms: 16 + r = 1 + 2r Solving 16 + r = 1 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. 16 + r + -2r = 1 + 2r + -2r Combine like terms: r + -2r = -1r 16 + -1r = 1 + 2r + -2r Combine like terms: 2r + -2r = 0 16 + -1r = 1 + 0 16 + -1r = 1 Add '-16' to each side of the equation. 16 + -16 + -1r = 1 + -16 Combine like terms: 16 + -16 = 0 0 + -1r = 1 + -16 -1r = 1 + -16 Combine like terms: 1 + -16 = -15 -1r = -15 Divide each side by '-1'. r = 15 Simplifying r = 15
| 4x+6=x-2y | | 4x+x=51 | | X-2(2x-7)=2(x-8) | | 186x=1132-16 | | abs(3x+4)=-3 | | w-(-8)=47 | | -4.8=3.2 | | 25+10(12-x)=5(3x-7) | | 41x-12(x-4)= | | 20=20*log(x) | | 7x+17x-7=6(4x+10) | | x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 | | 0.5x+3=0.75-7.75 | | -5(6k+9)=-27+7k | | 20=20log(x) | | 0.4-0.107= | | 78=1/2h(5+8) | | 5.6x+3=4.6x | | 2x-(6x-4)=8-4x | | 10-7x=-(x-12) | | 16x=-50 | | 3y-20=40 | | 8k-2=4 | | Y^2+3y=x^3-x | | 3w-4=4w | | 18(x+3)=2(9x+2)+50 | | 5b-3=-9 | | 4n+15=4n+15 | | 8x+7(-3x-6)=-52-3x | | 10x+18=3(3x+4) |